Pluralism in the perspective of Semitic religions - Biyanto Biyanto (Indonesian Journal of Islam and Muslim Societies, 2015)
This article  explores  the concepts of  religious pluralism  in  the perspective ofSemitic  religions:  Judaism, Christianity,  and  Islam. As Semitic  religions,  thethree actually share some teaching similarities in the field of theology.  But, inso a long history development,  it turns out that there are some differences  intheir  theological  teachings. The  power  history  and  politics  factors  have  alsoinfluenced  the relation between  the  followers of  the Semitic religions. There-fore,  it  is  important  to explore deeply  the concepts of pluralism  in  the  threereligions and also the development of the thoughts about the religious plural-ism among  the philosophers and  theologians  in  each of  the  religion. This  isdue  to  the  fact  that  in  this  present  context,  all  religions  in  this  globe  facesimilar problems dealing with the pluralism where one of the indicators is theoccurrence of  radicalism even  terrorism cases  involving  the  followers of eachreligion. The  triggering  factor  is    that  the  followers  of  each  religion  are notready  to  live  in  diversity.  It  is  due  to  the  high  amount  of  socio-religion-nu-anced radicalism cases that a number of thinkers from the three religions havebeen  trying  to    reformulate  the meanings of pluralism  in  the present contextwith  the  target  to have  some active  involvements among  the  followers of  theSemitic  religions  to  solve  the  plurality  problem. At  present  there  is  someawareness  among  the  thinkers  that  each  group  of  religion  should  not  have some  thoughts  that  they  are  the  best,  and  it  is  only  they  that  possess    theheaven. Such a claim  is growing  from a group’s subjectivity. If this happens,  itmeans that there is a threat to any efforts in implanting the values of pluralism.Artikel  ini membahas konsep pluralisme keagamaan dalam perspektif agama-agama semitik, yakni Yahudi, Kristen, dan Islam. Sebagai agama semitik atauagama  samawi,  tiga  agama  tersebut  sebenarnya memiliki  kesamaan  ajaran dibidang teologi. Tetapi dalam perkembangan sejarah yang begitu panjang ternyataada beberapa ajaran teologi yang berbeda. Faktor sejarah dan politik kekuasaanjuga  berpengaruh  terhadap  hubungan  pemeluk  tiga  agama wahyu  tersebut.Karena  itu  penting  ditelaah  secara mendalam  konsep  pluralisme  tiga  agamatersebut.  Juga  penting  dibahas  perkembangan  pemikiran  tentang  pluralismekeagamaan  di  kalangan  filsuf  dan  teolog  dari masing-masing  agama.  Sebab,dalam konteks kekinian semua agama di dunia ini menghadapi problem yangsama berkaitan dengan pluralisme. Diantara indikatornya, masih sering terjadikasus radikalisme, bahkan terorisme, yang melibatkan pemeluk masing-masingagama.  Jika  dlacak  faktor  pemicunya  adalah  ketidaksiapan  pemeluk masing-masing  agama untuk hidup dalam kemajemukan. Seiring dengan banyaknyakasus  radikalisme  sosial  bernuansa  agama  itulah  sejumlah  pemikir  dari  tigaagama  semitik  tersebut  telah  berupaya  untuk merumuskan  kembali maknapluralisme dalam konteks kekinian. Targetnya adalah adanya keterlibatan yangaktif  antarpemeluk  agama  semitik  untuk mengatasi  problem  pluralitas. Kiniada kesadaran di kalangan pemikir agama-agama semitik bahwa setiap kelompoktidak dibenarkan merasa paling unggul dan menganggap kelompok lain tidakberarti. Juga  tidak dibenarkan ada klaim kebenaran bahwa surga hanya milikkelompok  tertentu. Klaim  tersebut  jelas  tumbuh dari  subjektifitas kelompok.Jika  itu  terjadi  berarti  ancaman  terhadap  usaha  untuk membumikan  nilai-nilai  pluralisme.